‏عمان واليابان تبادل الثقافي مشغول بين البلدين - Endo, Haruo (ذاكرة عمان, 2018)
Keywords: Relations – Oman – Japon

Ceremony held at Tokyo University on donation of books by Sultanate of Oman (Arab News Japan, 2022)
Arab News JapanTOKYO: A ceremony was held on Friday to ・・・
Keywords: Relations – Oman – Japon